2001
DOI: 10.1046/j.1440-1711.2001.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of hepatitis C virus infection

Abstract: Summary Hepatitis C virus, a recently identified member of the family Flaviviridae, is an important cause of chronic viral hepatitis and cirrhosis. There are similarities in the nature of the immune response to this pathogen with immunity in other flavivirus and hepatotropic virus infections, such as hepatitis B. However, the high rate of viral persistence after primary hepatitis C infection, and the observation that neutralizing antibodies are not protective, would suggest that there are a number of important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 371 publications
(418 reference statements)
3
62
0
2
Order By: Relevance
“…Most vaccines promote the production of neutralizing antibodies that offer protection against acute viral infections (24,47). In the context of chronic infections (e.g., hepatitis C virus and human immunodeficiency virus [HIV] infections), neutralizing antibodies are potent in controlling free viral particles but are usually inefficient at eliminating infected cells (4,9,19). Recognition and destruction of infected cells by specific cytotoxic T lymphocytes (CTLs) are essential for carrying out an effective battle against such viruses.…”
mentioning
confidence: 99%
“…Most vaccines promote the production of neutralizing antibodies that offer protection against acute viral infections (24,47). In the context of chronic infections (e.g., hepatitis C virus and human immunodeficiency virus [HIV] infections), neutralizing antibodies are potent in controlling free viral particles but are usually inefficient at eliminating infected cells (4,9,19). Recognition and destruction of infected cells by specific cytotoxic T lymphocytes (CTLs) are essential for carrying out an effective battle against such viruses.…”
mentioning
confidence: 99%
“…Antigenic peptides derived from the cleavage of exogenous viral proteins are recognized by CD4+ T-helper cells in association with MHC class II molecules on the surface of APC. T-helper lymphocytes have an immunoregulatory function through the secretion of lymphokines that support either Cytotoxic T Lymphocyte (CTL) generation (the T-helper type 1 cytokine profile: IL-2, IFN-Îł) or B-cell function and antibody production (the type 2 profile: IL-4, IL-5, IL-10) [6].…”
Section: Hepatitis Cmentioning
confidence: 99%
“…However, a number of viruses like Theiler's murine encephalomyelitis virus or the neurotropic JHM strain of mouse hepatitis virus are able to establish a persistent infection in the central nervous system (CNS) despite strong primary CD8 + T cell responses in mice [1][2][3]. In humans, hepatitis B virus (HBV) and hepatitis C virus as well as HIV are able to maintain a chronic infection in the face of high numbers of antiviral CD8 + T cells, leading to liver immunopathology or immune system dysfunction [4][5][6][7]. In patients persistently infected with HIV, it was shown that HIV-specific CD8 + T cells have impaired cytolytic activity [8].…”
Section: Introductionmentioning
confidence: 99%